Pengaruh Return on Equity dan Intensitas Modal terhadap Tax Avoidance dengan Corporate Governance sebagai Variabel Moderasi: The Effect of Return on Equity And Capital Intensity on Tax Avoidance with Corporate Governance as a Moderating Variable - Yuniarti, Setiafitrie; Setianda, Rizky Aldi; Fatimah, Siti (Nusantara Journal of Education and Social Science, 2024)
This study examines the effect of Return on Equity, Capital Intensity on Tax Avoidance with Corporate Governance (proportion of independent board of commissioners) as a moderation variable. Using the Purposive Sampling method, as many as 7 selected companies met the sample selection criteria from a total of 24 agricultural sector companies listed on the Indonesia Stock Exchange during 2017 – 2021 so that the total sample was 35 samples. Using multiple linear regression analysis, the results showed that Return on Equity has a significant negative effect on Tax Avoidance, Capital Intensity has a significant positive effect on Tax Avoidance. In contrast to the existence of Corporate Governance as a moderation variable, Corporate Governance (the proportion of independent board of commissioners) actually has a positive but not significant effect on the relationship of Return on Equity to Tax Avoidance. In addition, Corporate Governance actually has a significant negative influence on the relationship of capital intensity to Tax Avoidance